Lessons learned from large construction project in Saudi Arabia - Mitra, S.; Tan, Albert (Emerald Group Publishing, 2012)
The purpose of this paper is to identify project management issues in a specific construction project in Saudi Arabia, highlighting its unique context. In the tradition of phenomenological research, a framework based deductive research approach is adopted where a structured questionnaire is used in one?to?one interview with project participants. This research highlights the interaction outcomes of human, project tool & methods, supply chain and finance affecting overall project execution and goes beyond to identify critical linkages in these interactions, including those that will need identification of skill sets required for the project manager's role, options approach and standardization of product and processes together with early involvement of diverse stakeholders in the project for their better execution through ex ante identification of project parameters requiring minimum changes. The final framework arrived at identifies various tradeoffs involved in project management in the idiosyncratic context of demanding client driving the project needs and internal resistance to change limiting flexibility in project execution. It focuses on deviations from international project execution standards, as found in large construction projects in the Middle East, specifically Saudi Arabia. The limitation of the research lies in arriving at generalizable findings based on the study of a single international hotel construction project, and not an industry?wide questionnaire survey which can, in future, refine and strengthen the framework developed. A study in the context of Saudi Arabia is seldom reported in international journals although large turnkey construction project opportunities exist for international firms in this country and in the Middle East region. © 2012, Emerald Group Publishing Limited